OPTIMALISASI KENAIKAN BERAT BADAN BAYI USIA 0-6 BULAN MELALUI PIJAT BAYI - indriati, maya; Laily, Rahima Fajri (Jurnal Sehat Masada, 2025)
Baby massage is the oldest known touch therapy and is known to have many benefits. One of them is to increase the baby's weight. Massage will increase the tone of the vagus nerve so that food absorption becomes faster. The purpose of this study was to determine the effect of baby massage on increasing body weight in infants aged 0-6 months. This research design uses a type of pre-experiment research. The population in this study were 32 babies aged 0-6 months who were massaged, for data processing using the T test. The results showed that of the 32 respondents with an average weight before baby massage of 4171.88 grams and after baby massage of 4909.38 grams the results of the statistical test obtained were that there was an effect of baby massage on increasing body weight in infants aged 0-6 months at TPMB E Bandung City with the results of P Value 0.000. Based on the results of this study, it is hoped that parents can do massage regularly and choose baby massage as an alternative to increase baby weight.